The Would-Be Technocracy: Evaluating Efforts to Direct and Control Social Change with Internet Protocol Design - Badiei, Farzaneh; Fidler, Bradley (Journal of information policy (University Park, Pa.), 2021)
This article discusses the shortcomings of value in design approach to protect human rights on the Internet. It argues that Internet protocols do not single handedly mitigate human rights on the Internet and in order to measure their impact, they need to be put in context. In other words, instead of design determinism, contextual analysis of Internet technologies that involve Internet protocols should take place.